The Assessment Effect of Spiritual Care on Hopelessness and Depression in Suicide Attempts - Heidari, Mohammad (Journal of religion and health, 2019)
The purpose of this study was to assess the effect of spiritual care on hopelessness and depression among suicide attempts. This semi-experimental study that 60 suicide attempts and these samples were divided in to two cases and control groups. For case group, service package of spiritual care was designed and conducted during their visits to psychiatrists' offices. Findings showed that there was a significant difference after performing spiritual care in depression in both groups (X2 = 22, P = 0.002) and their hopelessness (X2 = 20, P = 0.001). The use of spiritual intervention is suggested in order to implement holistic nursing care during treatment should be considered as a matter of principle.